Combined Stereotactic Body Radiotherapy and Checkpoint Inhibition in Unresectable Hepatocellular Carcinoma: A Potential Synergistic Treatment Strategy - Chiang, Chi-Leung; Chan, Albert C. Y.; Chiu, Keith W. H.; Kong, Feng-Ming (Spring) (Frontiers in Oncology, 2019)
Background: Current treatments of unresectable hepatocellular carcinoma (HCC) are trans-arterial chemo-embolization (TACE), stereotactic body radiotherapy (SBRT), and targeted therapy. However, these treatments are limited in efficacy and safety for patients with large tumor sizes. Here, we report a case series of combined SBRT and anti-PD-1 therapy in patients with unresectable HCC of large tumors. Methods: This is a retrospective case series of 5 patients with unresectable hepatocellular carcinoma who were treated with SBRT followed by anti-PD1 antibodies. Four patients (80%) received a single dose of TACE prior to SBRT. All patients had advanced HCC ineligible of curative intervention. In this study, we report their treatment responses according to modified RECIST (response evaluation criteria in solid tumor) criteria, 1-year local control (LC), progression-free survival (PFS), 1-year overall survival (OS) rate, and toxicities. Results: Among the five evaluated patients, 3 patients had underlying diseases of hepatitis B and 4 patients had Barcelona clinic liver cancer stage C. The median size of their tumors was 9.8 cm (range: 9-16.1cm). In addition, 2 patients had tumor vascular thrombosis and one had extra-hepatic disease. Five out of 5 patients (100%) responded to treatment, with 2 complete responses (CR) and 3 partial responses (PR). Among the partial responders, one had a down-staged tumor that became amenable for radiofrequency ablation for tumor clearance. No patient developed tumor progression at the time of analysis during the median follow-up of 14.9 months (range 8.6-19 months). The median PFS was 14.9 months (range: 8.6-19 months); 1-year LC and OS rate were both 100%. One patient had grade ≥ 3 toxicities (pneumonitis and skin reaction). There was no classical radiation-induced liver disease. Conclusions: The results obtained from these 5 cases demonstrate impressive tumor control from the combination of SBRT and checkpoint inhibitors in patients with large tumors of advanced HCC. Further prospective trials are warranted.